Effects of Computer-Animation among NCE Students’ of Different Ability Levels in Biology Concepts in Bauchi State, Nigeria - Ahmed Nasiru Ala; Amos Ochayi Onojah; Abdullahi Mohammed Isyaku; hu'Aibu Bala Adamu (International Journal of Education, Teaching, and Social Sciences, 2023)
Computer-animation is the use of computer device to create an illusion of moving images in sequential form. Computer-animations, when effectively used in teaching abstract and complex concepts especially in Biology, better performance could be granted. This study investigated the effects of computer-animation on NCE students with different ability levels in Biology concepts in Bauchi State, Nigeria. The objective of the study was to determine the effects of ability levels on NCE students’ performance when taught biology concepts using computer-animation-package. The study adopted quasi-experimental design. The population for this study comprised 2,594 Biology students in colleges of education in Bauchi State, while the target population was 878 NCE II Biology students. There are four NCE-awarding institutions in the State of which only two run Biology Education programme at the NCE level. Sixty NCE II Biology students participated (42 for experimental of 21 males, 21 females taught using animation-package and 18 for control group of 9 males and 9 females taught with lesson note). Six instruments were developed: animation-package, questionnaire, lesson notes, to-do lists, manual and test. The 6 instruments were validated but only the animation-package test items were pilot tested for reliability. The results were 0.432 for pretest, and 0.001 for posttest. Mean and standard deviation were used to answer research question. Analysis of Variance at 0.05 level of significance. The findings of the study revealed no significant difference in the performance of high ability, medium ability and low ability levels students, when taught biology concepts using computer-animation. The study concluded that computer-animation strategy enhanced NCE students’ academic performance in biology concepts irrespective of their ability levels. The implication is that computer-animation instructional strategies played significant role in the teaching and learning biology concepts among students with different ability levels in colleges of education in Bauchi State, Nigeria. The study recommended that lecturers of Biology in colleges of education to incorporate computer-animation into their teaching